Made in Canada, Read in Spain: Essays on the Translation and Circulation of English-Canadian Literature - Somacarrera, Pilar (De Gruyter, 2013)
Made in Canada, Read in Spain is an edited collection of essays on the impact, diffusion, and translation of English Canadian literature in Spain. Given the size of the world's Spanish-speaking population (some 350 million people) and the importance of the Spanish language in global publishing, it appeals to publishers, cultural agents and translators, as well as to Canadianists and Translation Studies scholars. By analyzing more than 100 sources of online and print reviews, this volume covers a wide-range of areas and offers an ambitious scope that goes from the institutional side of the Spanish-Anglo-Canadian exchange to issues on the insertion of CanLit in the Spanish curriculum; from 'nation branding', translation, and circulation of Canadian authors in autonomous communities (such as Catalonia) to the official acknowledgement of some authors by the Spanish literary system -Margaret Atwood and Leonard Cohen were awarded the prestigious Prince of Asturias prize in 2008 and 2011, respectively.